Comprehensive Analysis for Histone Acetylation of Human Colon Cancer Cells Treated with a novel HDAC Inhibitor - Zhao, Yunlong; Fang, Xiuli; Wang, Ye; Zhang, Junmei; Jiang, Sheng; Liu, Zhe; Ma, Zhenyi; Xu, Liyan; Li, Enmin; Zhang, Kai (Current Pharmaceutical Design, 2014)
Extensive evidence suggests that dysregulation of histone lysine acetylation is intimately linked with the development of cancer in epigenetic level. Histone acetylation on lysine is regulated mainly by the
Keywords: lysine acetylation